Study on modular smoke extraction with solid screen in urban road tunnel fires - Xiaotao Zhang; Kaihua Lu; Yushi Lu (PLoS ONE, 2026)
A series of numerical simulations were conducted to evaluate and optimize a modular smoke extraction system integrated with smoke screens for urban road tunnel fires. The study aimed to identify key design parameters and propose optimal strategies for tunnel-wide smoke management. The results show that smoke screen height is a critical factor, with a threshold of 1.5 m (25% of tunnel height) significantly enhancing extraction efficiency and reducing high-temperature zones, while vent-screen distance has minimal impact. Dividing the tunnel into five modular zones achieves the optimal balance between hazard control and system cost. Furthermore, an unbalanced airflow distribution strategy—allocating 35% of the total exhaust volume (180 m³/s) to proximate vents and 15% to distal vents—proves most effective in preventing plug-holing phenomenon and maximizing CO extraction efficiency. These findings provide specific design thresholds and actionable strategies for the optimization of transverse smoke extraction systems in urban road tunnels.